Proceedings of the 40th International Conference on Software Engineering 2018
DOI: 10.1145/3180155.3180239
|View full text |Cite
|
Sign up to set email alerts
|

Identifying design problems in the source code

Abstract: The prevalence of design problems may cause re-engineering or even discontinuation of the system. Due to missing, informal or outdated design documentation, developers often have to rely on the source code to identify design problems. Therefore, developers have to analyze different symptoms that manifest in several code elements, which may quickly turn into a complex task. Although researchers have been investigating techniques to help developers in identifying design problems, there is little knowledge on how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…In the studies of Fontana et al [66], [67], they described three representative architecture smells and presented a tool, Arcan, to support their detection. Instead of investigating detection techniques, Sousa et al's work [68] focused on how developers actually proceed to identify design problems by using the design problem symptoms.…”
Section: Related Workmentioning
confidence: 99%
“…In the studies of Fontana et al [66], [67], they described three representative architecture smells and presented a tool, Arcan, to support their detection. Instead of investigating detection techniques, Sousa et al's work [68] focused on how developers actually proceed to identify design problems by using the design problem symptoms.…”
Section: Related Workmentioning
confidence: 99%
“…The harmful effects of design problems have led to the discontinuance or reengineering of some software systems 27,28 . Silva et al, 29 Xiao et al, 30 and Sousa et al 31 show that design issues are one of the most common categories of technical issues that lead to the failure of software systems. Therefore, given the negative effects of design problems, it is recommended that developers should remove them from software systems as early as possible 32,33 in the software development process.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Other studies have focused on investigating the identification of design problems from the perspective of developers as well [47,48]. Sousa et al [47] conducted a qualitative study to investigate how developers identify design problems in practice.…”
Section: Other Approaches To Identify Design Problemsmentioning
confidence: 99%
“…They also observed that developers often search for multiple symptoms of design problems, such as code smells, during the identification. In a subsequent study, Sousa et al [48] proposed a theory to describe how the identification of design problems happens in practice. Their theory explains factors that influence developers during the identification of design problems.…”
Section: Other Approaches To Identify Design Problemsmentioning
confidence: 99%